2012
DOI: 10.1073/pnas.1207806109
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of abrupt deglacial climate change on tropical Atlantic subsurface temperatures

Abstract: Both instrumental data analyses and coupled ocean-atmosphere models indicate that Atlantic meridional overturning circulation (AMOC) variability is tightly linked to abrupt tropical North Atlantic (TNA) climate change through both atmospheric and oceanic processes. Although a slowdown of AMOC results in an atmospheric-induced surface cooling in the entire TNA, the subsurface experiences an even larger warming because of rapid reorganizations of ocean circulation patterns at intermediate water depths. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
112
1
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(129 citation statements)
references
References 36 publications
13
112
1
3
Order By: Relevance
“…1). The Florida Current overlaying the core site is comprised of wind-driven recirculated gyre water (∼17 Sv) and cross-equatorial flow from the South Atlantic (∼13 Sv) (Schmitz and McCartney, 1993) forming the northward flowing surface branch of the AMOC. The waters in the Florida Current are sourced from the Caribbean, the tropical Atlantic, and western tropical South Atlantic, and travel through the Yucatan Straights and the Gulf of Mexico before reaching the Florida Straits (Murphy et al, 1999;Schmitz and Richardson, 1991).…”
Section: Regional Settingmentioning
confidence: 99%
“…1). The Florida Current overlaying the core site is comprised of wind-driven recirculated gyre water (∼17 Sv) and cross-equatorial flow from the South Atlantic (∼13 Sv) (Schmitz and McCartney, 1993) forming the northward flowing surface branch of the AMOC. The waters in the Florida Current are sourced from the Caribbean, the tropical Atlantic, and western tropical South Atlantic, and travel through the Yucatan Straights and the Gulf of Mexico before reaching the Florida Straits (Murphy et al, 1999;Schmitz and Richardson, 1991).…”
Section: Regional Settingmentioning
confidence: 99%
“…Modeling results in Schmidt et al . [] showed that a major reduction in AMOC under Last Glacial Maximum (LGM) forcings and boundary conditions can produce a strong subsurface warming in the western TNA and equatorial Atlantic, providing evidence this mechanism could have operated under glacial conditions. Schmidt et al .…”
Section: Introductionmentioning
confidence: 99%
“…Schmidt et al . [] also analyzed Mg/Ca ratios in the subthermocline dwelling planktonic foraminifera Globorotalia crassaformis in core VM12‐107 from the Southern Caribbean to reconstruct a record of deglacial subsurface temperature change (see Figure for core location). Their results showed significant subsurface warming at the start of the Younger Dryas and Heinrich event 1 that covaried with changes in AMOC variability across the deglacial, demonstrating a link between AMOC weakening and subsurface warming in the TNA, likely through the first step of the proposed mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Most climate models simulating slowing of AMOC transport (whether addressing global warming or past NACE events) produce a distinctive North Atlantic-South Atlantic SST anomaly dipole with much less change of the SST in the equatorial Atlantic region (e.g., Vellinga and Wood, 2002, Zhang and Delworth, 2005, Liu et al, 2009, Zhang et al, 2011, Menary et al, 2012and Schmidt et al, 2012). …”
Section: Periods Of Anomalous Warmth In the Northern Tropical Atlantimentioning
confidence: 99%